National STEAM Education Report Jamaica: Towards Developing a Strong STEAM Ecosystem - Burke, Amanda; Gray-Alvaranga, Sandra; Hull, Zayne; Hutton, Clinton; Johnson, Beverly; Philips, Robert; Baker-Gibson, Joy; Benjamin, Albert; Leon, Venesse; Morrison, Beth; Pinnock, Asburn; Sherriffe, Delmar (British Council, 2022)
This British Council commissioned report is based on an assessment of the current status of STEAM Education in Jamaica. Both public and private sector stakeholder groups were assessed. A key element of the report examines the extent to which existing STEAM education curricula are aligned with international benchmarks. A policy concept paper is included to guide the way forward. The British Council aims for the report to serve as a baseline from which to monitor, grow and shape the ecosystem for STEAM Education in Jamaica. The report consists of five sections, each covering an aspect of the STEAM ecosystem. Section I is an introductory section, which explores the concept of STEAM Education and its value to the nation. Section II explores the idea of a STEAM ecosystem for Jamaica, while Section III examines the challenges to developing such an ecosystem. An approach to overcoming the challenges, and related policy recommendations for doing so, are presented in Sections IV and V.